2003
DOI: 10.1080/0954012031000105450
|View full text |Cite
|
Sign up to set email alerts
|

Adherence issues in children and adolescents receiving highly active antiretroviral therapy

Abstract: The introduction of highly active antiretroviral therapies (HAART) for the treatment of paediatric HIV infection poses additional adherence challenges for children and families living with HIV A preliminary survey of 18 parents of children receiving HAART in Australia showed that although parents report high level of child adherence to HAART, specific features of the medication regimen, such as taste and number of medications made administration of HAART extremely difficult.Moreover, interaction between the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 9 publications
2
32
0
1
Order By: Relevance
“…These findings are consistent with earlier studies. (Boni, et al, 2000;Giacomet et al, 2003;Gibb et al, 2003;Goode et al, 2003;Martin et al, 2007;Pontali et al, 2001;Temple et al, 2001). While improving access to child-friendly formulations is vital, the use of simplified regimen, fixed dose combinations and less frequent dosing requirements, coupled with educating caregivers on the benefits and side effects of ART may also improve adherence (WHO, 2006; Working Group on Antiretroviral Therapy and the Medical Management of HIV-Infected Children, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with earlier studies. (Boni, et al, 2000;Giacomet et al, 2003;Gibb et al, 2003;Goode et al, 2003;Martin et al, 2007;Pontali et al, 2001;Temple et al, 2001). While improving access to child-friendly formulations is vital, the use of simplified regimen, fixed dose combinations and less frequent dosing requirements, coupled with educating caregivers on the benefits and side effects of ART may also improve adherence (WHO, 2006; Working Group on Antiretroviral Therapy and the Medical Management of HIV-Infected Children, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This technique does not use pre-set questions, but is shaped by a defined set of topics. The topics (Table 1) were informed by a literature review of published studies relevant to factors influencing adherence in children (Bikaako-Kajura et al, 2006;Boni et al, 2000;Elise et al, 2005;Giacomet et al, 2003;Gibb et al, 2003;Goode et al, 2003;Hammami et al, 2004;Marhefka et al, 2006;Martin et al, 2007;Mellins et al, 2004;Nicholson et al, 2006;Pontali et al, 2001;Reddington et al, 2000;Temple et al, 2001;Williams et al 2006). All interviews were conducted by the principal investigator who had no role in the clinical care provided at the organisation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Despite the importance of this issue, large multi-national pharmaceutical companies that have a monopoly on the manufacture of ARV drugs consider developing countries a poor market for their drugs.…”
Section: Discussionmentioning
confidence: 99%
“…From the parental perspective, earlier studies reported that parents prefer oral liquid to solid forms (eg, powder, tablets, capsules), but compliance was measured in only some studies. [50][51][52] A recent randomized study of infants and toddlers with malaria demonstrated superior adherence to a regimen of crushed tablets when compared with syrup. 53 In a study of children with HIV, caregivers reported that it was easier to administer the tablet form of a medication than a large volume of powder.…”
Section: Complexity Of Medication Schedulementioning
confidence: 99%